Centennial anniversary of the Saratov research association of dermatologists and venereologists - A. I. Zavyalov; S. R. Uts; V. F. Orkin; A. V. Morrison (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article describes major historic stages of the Saratov Research Association of Dermatologists and venereologists. The authors describe the Society's role in the establishment and development of the dermatovenerological service, health education, prevention and improvement of measures aimed at fighting sexually transmitted and contagious skin diseases as well as training highly skilled personnel and promoting health care services in the region.